Citizenship and social class - Marshall, T.H. (London Pluto Press, 1992)
Over forty years after it first appeared, T.H. Marshall's seminal essay on citizenship and social class in postwar Britain has acquired the status of a classic. His lucid analysis of the principal elements of citizenship -- namely, the possession of civil, political and social rights -- is as relevant today as it was when it first appeared. It is reissued here with a complementary monography by Tom Bottomore in which the meaning of citizenship is re-examined, in very different historical circumstances. In asking how far the prospects for class equality have been realised, Bottomore continues the discussion in a context that encompasses the restoration of civil and political rights in Eastern Europe, problems of welfare capitalism, citizenship and the nation state and the broader issues of equality and democratic institutions.
Includes index
Keywords: Citizenship